Knowledge, attitude and practice on fast food consumption among normal and overweight/obese International Islamic University Malaysia Kuantan students - Azman, Siti Ainun Muti'ah; Ibrahim, Muhammad Ariff; Azahari, Nuraniza (IIUM Press, 2020)
Increase in the number of restaurants will directly or indirectly influence the students to consume fast foods. The number of fast food outlets is significantly increased in the area of Bandar Indera Mahkota which is near to International Islamic University of Malaysia (IIUM) Kuantan campus. Hence, students can easily access to fast food. Additionally, fast food consumption may be associated with the body mass index (BMI) of the students. The main objective of this study is to identify the knowledge, attitude and practice of fast food consumption among normal and overweight/obese IIUM Kuantan students.